THE DYNAMIC ROLE OF COMMITMENT AND TRUST IN THE DEVELOPMENT OF JUVENILE REHABILITATION POLICIES - Intan Fitri Meutia; Novita Tresiana; Muhammad Shafwan Assalam (Universitas Lampung, 2025)
This research examines the critical role of commitment and trust in the development of Child Rehabilitation Centers in Indonesia, with a specific focus on the Special Child Development Institution Class II in South Sumatra. It explores child welfare and rehabilitation within the juvenile justice system, highlighting key legal and practical challenges, including the gap between regulatory frameworks and field implementation, inadequate stakeholder coordination, and the absence of standardized rehabilitation procedures. The research investigates stakeholder commitment, encompassing government institutions, policymakers, juvenile justice professionals, and community members, while also analyzing the formation and maintenance of trust and its impact on rehabilitation effectiveness. Using an empirical qualitative approach, data is collected through interviews with correctional officers and children in the institution to capture their experiences, challenges, and expectations, alongside a review of relevant literature, policies, and legal frameworks. This research aims to identify legal barriers in child rehabilitation and propose policy recommendations to strengthen the rehabilitation and reintegration system for children in conflict with the law. The findings offer practical insights for policymakers and practitioners in designing rehabilitation strategies that align with national and international legal standards while safeguarding children's rights within Indonesia’s juvenile justice system.